Establishing Guidelines to Improve the High-Pressure Die Casting Process of Complex Aesthetics Parts - Silva, F.J.G. (2020)
Zamak is a light-weight alloy presenting very good properties for parts not requiring high mechanical strength. Due to its low melting temperature, this alloy is perfectly suitable for complex shape parts because it is easily moulded by high-pressure die casting process. Industrial parts usually do not require perfect look but this alloy can be also suitable for aesthetic parts, requiring complex finishing processes.The challenge embraced by this work aims to optimize the injection parameters and mould configuration of a Zamak alloy aesthetic part, to be obtained through a single injected casting operation, minimizing finishing operations. In order to obtain healthy, defect-free Zamak parts with a good aesthetic appearance, it was necessary to study the problem and then try to find the best possible solution. Thus, a study was carried out about the high-pressure die casting process and corresponding parameters. Throughout the work, and in order to solve the problem, numerical simulations were carried out using the SolidCast™ software, studying the material flow into the mould and corresponding fusion lines, and empirical tests were carried out in order to correlate the results with the parameters. Changes in the mould were also performed. After the experiences, it was possible to draw some guidelines in order to achieve better results in the Zamak high-pressure die casting process of complex aesthetic parts, allowing for save time in next approaches.